Utility of the ECG-Based Simple Score for Predicting Post-Stroke Atrial Fibrillation in a Real-World Clinical Setting - Yusuf Hosoglu MD; Ayse Hosoglu MD; Veysi Kavalcı MD; Hakan Tibilli MD; Sezer Markirt MD; Erman Altınışık MD (Clinical and Applied Thrombosis/Hemostasis, 2025)
Background Atrial fibrillation (AF) significantly increases the risk of ischemic stroke and often remains asymptomatic until stroke onset. Identifying stroke survivors at high risk for incident AF is critical for targeted anticoagulation therapy. This study aimed to evaluate the predictive utility of the ECG-based SIMP3L2E score alone and combined with Holter-detected supraventricular ectopy for incident AF and recurrent stroke in ischemic stroke survivors. Methods This prospective observational study enrolled 77 patients hospitalized with acute ischemic stroke between January and September 2021. Although the SIMP3L2E score was published in 2024, all required ECG parameters were collected prospectively during initial hospitalization and retrospectively calculated for analysis. Incident AF and recurrent strokes were assessed retrospectively over a three-year follow-up. Predictive performance was evaluated using logistic regression and receiver operating characteristic (ROC) analysis. Results Of the participants, 27 (35.1%) had high SIMP3L2E scores (≥12). Incident AF occurred in 12 patients (15.6%) and recurrent stroke in 9 patients (11.7%). The SIMP3L2E score alone had modest predictive ability (AUC = 0.588). However, supraventricular ectopy detected by Holter was independently predictive of incident AF (OR: 0.092; 95% CI: 0.016-0.538; p = .008) and significantly improved predictive accuracy (AUC = 0.797). Conclusion The SIMP3L2E ECG score demonstrated limited predictive power alone in older post-stroke patients but showed substantially improved discrimination when combined with Holter-detected supraventricular ectopy. Integrating static ECG scores with dynamic rhythm monitoring could enhance risk stratification for incident AF following ischemic stroke. Future studies should validate these findings in larger, diverse populations.